Impact of MHC mismatches on the development of early posttransplant acute heart rejection - S. V. Spiridonov; A. I. Tsyrkunov; M. G. Koliadko; I. S. Sivets; Yu. P. Ostrovsky (Вестник трансплантологии и искусственных органов, 2025)
Objective: to analyze the impact of MHC mismatches, considering recipient nationality and age, on the develop- ment of rejection crisis.Material and methods. A retrospective study was conducted, including 264 recipients and their 264 matched donors. HLA typing was performed by serological and molecular genetic (SSP) methods. Mismatches in the following MHC class I and II genes were assessed: HLA-A, HLA-B, HLA-DRB1, HLA- DQB1. Recipient age and nationality were also considered in the analysis.Results. MHC Class I mismatches (HLA-A, HLA-B) did not significantly impact the occurrence of acute rejection crises. MHC Class II mismatches (HLA-DRB1, HLA-DQB1) significantly increased the risk of acute rejection (χ2 = 6.790; df = 1; p = 0.009), with an odds ratio (OR) of 5.69 (95% CI: 1.32–24.50). Recipient age had a significant effect on acute rejection (χ2 = 8.200; df = 1; p = 0.004). Recipients under 45 years experienced rejection in 34.8% of cases, 18.9% more than those aged 45 and older, with an OR of 2.30 (95% CI: 1.29–4.10). Donor-recipient nationality mismatch signifi- cantly influenced acute rejection (χ2 = 4.660; df = 1; p = 0.031), with an OR of 2.00 (95% CI: 1.06–3.79). The analysis, considering all three above-mentioned factors, confirmed that MHC mismatches significantly influence the development of acute graft rejection in Belarusian recipients under 45 years old (χ2 = 4.068; df = 1; p = 0.044) and in recipients of other nationalities (Russians, Israelis, Georgians, Armenians, Uzbeks, Kazakhs, Azerbaijanis, Ukrainians) under 45 years old (χ2 = 4.342; df = 1; p = 0.037). Among Belarusian recipients, no cases of rejec- tion were observed with 0–1 MHC mismatches, while rejection occurred in 35.4% of cases with 2–4 mismatches (OR 9.44, CI 0.51–173.61). Similarly, in recipients of other nationalities, acute rejection did not develop with 0–1 mismatches, but occurred in 50.0% of cases with 2–4 mismatches (OR 11.00, CI 0.56–217.69).Conclusion. It has been reliably established that MHC class II mismatches, donor-recipient nationality differences, and recipient age under 45 years significantly increase the risk of acute rejection crisis in the postoperative period.